Visual Design of Landscape Architecture Based on High-Density Three-Dimensional Internet of Things. (24th May 2021) - Chen, Jue
Abstract : Since different equipment manufacturers may define a set of data transmission protocols of their own types, the high-density three-dimensional Internet of Things landscape garden landscape platform needs to provide a unified data transmission interface for the business system. It needs to complete the analysis, storage, and reformatting of different data transmission protocols on the high-density three-dimensional Internet of Things landscape service platform. In this paper, based on the conversion analysis between the MLD model of the landscape perception layer of the high-density three-dimensional Internet of Things landscape and the automata scheduling model, the conversion of the MLD model of the entire landscape perception layer of the high-density three-dimensional IoT landscape and the automata scheduling model is realized. Based on the hierarchical automata high-density three-dimensional Internet of Things landscape, this paper studies the global task scheduling and control automata model and the local scheduling automata model in the task, as well as the landscape perception layer rapid scheduling mechanism of independent scheduling strategy. This can be used for different levels of systems to ensure that the perception layer system is orderly, reliable, and fast. They complete the construction of jdk environment, web server, Mongo DB server, MQTT server, JMS server, etc., on the cloud platform. Combined with the landscape, a set of test platforms was built to test the functions and performance indicators of the visualization system cloud platform. The test results show that the cloud platform can realize cross-platform terminal access, end-to-end instant messaging, heterogeneous data processing and storage, etc. It has strong scalability and high processing performance and has application and reference value.